Soil Capillary Depression In Lnapl Contaminated Soil Due To Fluctuating Groundwater Table Studies - Teo, Ka Meng (Universiti Sains Malaysia, 2021)
Oil spills are a typical occurrence that occurs all around the world. All sectors in Malaysia rely largely on oil as a source of energy. As a result, oil spills can happen easily during oil transportation, storage, production, and processing due to pipeline and underground storage tank leaks. Once the oil reaches the groundwater table, it can change the properties of the soil and pollute the water. The less-dense oil than water will usually float on the surface and migrate with the groundwater. Polluted soil and groundwater will have an impact on the environment. As a result, remedial work to clear the contaminated soil and groundwater is required. The cost of soil pollution treatment is typically considerable. The tracing technique for an oil spill over a vast area is also complex and costly. As a result, the migration of Light Non-Aqueous Phase Liquids (LNAPLs) in the soil can be investigated. Other than the migration pattern, the capillary fringe also plays an important role in LNAPL migration. The contaminated area of the ground may be predicted using knowledge of oil migration in soil, allowing for a more precise repair. Two-dimensional tank tests were used to investigate the lateral migration of diesel in this investigation. To investigate capillary depression in the soil, several groundwater table fluctuation patterns were simulated. In addition, the volume of oil spilled relationship was investigated in this study. Simplified Image Analysis Method was used to observe the saturation profile of LNAPL and water in the soil sample.